Gra, zabawa, przyjemność. Dlaczego "Playbook" Tomasza Bąka jest "entertaining"? - Trusewicz, Szymon (Zagadnienia Rodzajów Literackich, 2025)
The article discusses Tomasz Bąk’s Playbook, analysing it as a poetic volume that thematises basketball in the context of variously understood ideas of play and performance. The author of the text examines how Bąk uses stylisation and intertextuality, in particular to paraphrase Charles Dickens’ A Christmas Carol. Michael Jordan takes on the role of Ebenezer Scrooge, while his former teammate Scottie Pippen becomes Jacob Marley. Also emphasised is the volume’s stylistic polycentricity, incorporating Polish cultural references, and its performative nature, enhanced by graphic design and footnotes that create a parallel narrative about the NBA. The title itself refers to the idea of play and fun and, in line with the English meaning of the word “play,” to “joy” and “entertainment.” The performative nature of the work is crucial. Playbook is not only about basketball or capitalism, but is itself a performance that violates the boundaries of genres and languages. It engages the viewer and performs the reality of sport in late capitalism and of poetry itself. The concept of play is reinforced by the graphic design of the book by Bogna Brewczyk, which resembles a sports playbook with diagrams and symbols. The text suggests that the strategy of poetainment, by prioritising the enjoyment derived from the text, makes it possible to broaden the audience. While maintaining the entertaining nature of the volume, Bąk problematises the world of late capitalist sport and the image of poetry and the poet.